2017
DOI: 10.3724/sp.j.1123.2017.03018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of large-pore silica microspheres using templating method and their applications to protein separation with high performance liquid chromatography

Abstract: Large-pore silica microspheres were synthesized by utilizing weak cation exchange polymer beads as templates, -trimethoxysilylpropyl--trimethylammonium chloride (TMSPTMA) as a structure-directing agent, tetraethoxysilane (TEOS) as a silica precursor, and triethanolamine as a weak base catalyst. The hydrolysis and condensation of the silica precursors occurred inside the templating polymer beads yielded polymer/silica composite microspheres. After the organic polymer templates were removed in the calcination st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nevertheless, when noncrosslinked or slightly crosslinked macroporous polymeric beads were used as the templates in above studies, the formed silica spheres had the similar size to the templates, these methods were still limited in the creation of silica microspheres with ultra‐large pore size. In our recent study , we found that highly crosslinked polymeric beads could be used as the templates to synthesize ultra‐large pore silica microspheres that showed promising protein separations in HPLC after C18 silane bonding on the silica surface. In this study, we prepared the silica microspheres with a broad pore size distribution using the newly developed templating technique, and evaluated the as‐prepared silica microspheres as the supports for the coating of cellulose tris(3,5‐dimethylphenyl carbamate) to prepare chiral stationary phases for enantiomer separations in HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when noncrosslinked or slightly crosslinked macroporous polymeric beads were used as the templates in above studies, the formed silica spheres had the similar size to the templates, these methods were still limited in the creation of silica microspheres with ultra‐large pore size. In our recent study , we found that highly crosslinked polymeric beads could be used as the templates to synthesize ultra‐large pore silica microspheres that showed promising protein separations in HPLC after C18 silane bonding on the silica surface. In this study, we prepared the silica microspheres with a broad pore size distribution using the newly developed templating technique, and evaluated the as‐prepared silica microspheres as the supports for the coating of cellulose tris(3,5‐dimethylphenyl carbamate) to prepare chiral stationary phases for enantiomer separations in HPLC.…”
Section: Introductionmentioning
confidence: 99%